2017
DOI: 10.1111/1462-2920.13773
|View full text |Cite
|
Sign up to set email alerts
|

Manganese transport is essential for N2‐fixation by Rhizobium leguminosarum in bacteroids from galegoid but not phaseoloid nodules

Abstract: Summary Rhizobium leguminosarum has two high‐affinity Mn2+ transport systems encoded by sitABCD and mntH. In symbiosis, sitABCD and mntH were expressed throughout nodules and also strongly induced in Mn2+‐limited cultures of free‐living cells. Growth of a sitA mntH double mutant was severely reduced under Mn2+ limitation and sitA and mntH single mutants were more sensitive to oxidative stress. The double sitA mntH mutant of R. leguminosarum was unable to fix nitrogen (Fix‐) with legumes belonging to the galego… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 66 publications
(91 reference statements)
1
12
0
Order By: Relevance
“…During early root hair infection, S. meliloti is exposed to the reactive oxygen species (ROS) released by the plant host as a defense response ( Soto et al, 2009 ). Manganese has been shown to be important to counteract ROS effects, whereas Mg 2+ transport is essential for microaerobic nitrogen-fixation in late symbiotic stages ( Davies and Walker, 2007 ; Hood et al, 2015 ; Hood et al, 2017 ). It is therefore tempting to speculate on a key role of divalent metal ions in the control of Sm RNase III activity in vivo .…”
Section: Discussionmentioning
confidence: 99%
“…During early root hair infection, S. meliloti is exposed to the reactive oxygen species (ROS) released by the plant host as a defense response ( Soto et al, 2009 ). Manganese has been shown to be important to counteract ROS effects, whereas Mg 2+ transport is essential for microaerobic nitrogen-fixation in late symbiotic stages ( Davies and Walker, 2007 ; Hood et al, 2015 ; Hood et al, 2017 ). It is therefore tempting to speculate on a key role of divalent metal ions in the control of Sm RNase III activity in vivo .…”
Section: Discussionmentioning
confidence: 99%
“…Higher DCu concentrations could support denitrification in the coastal sediment and anoxic waters, removing bioavailable nitrogen and creating conditions favorable to N 2 fixation. Manganese has been shown to be essential for some terrestrial N 2 -fixing bacteria [76,77], but the physiological requirement for manganese in marine diazotrophs is not well understood.…”
Section: Factors Controlling the Distribution Of N 2 Fixationmentioning
confidence: 99%
“…In young nodules of galegoid-clade legumes, mntH and mntABC were found to be highly expressed in the plant symbiont Rhizobium leguminosarum (Hood et al . 2017 ). Interestingly, both genes appeared essential for nitrogen fixation, and their expression was only upregulated in galegoid-clade and not in phaseloid-clade legumes.…”
Section: Roles Effects and Functional Origin Of Mn 2+ Transport And Homeostasis In Bacteriamentioning
confidence: 99%
“…It was suggested that this host effect is related to a difference in Mn 2+ availability and/or ROS concentration in the different plant species (Hood et al . 2017 ).…”
Section: Roles Effects and Functional Origin Of Mn 2+ Transport And Homeostasis In Bacteriamentioning
confidence: 99%